The Central Role of Hypothermia and Hyperactivity in Anorexia Nervosa: A Hypothesis - Smith, Lucille Lakier (Frontiers in Behavioral Neuroscience, 2021)
Typically, the development of anorexia nervosa (AN) is attributed to psycho-social causes. Several researchers have recently challenged this view and suggested that hypothermia and hyperactivity (HyAc) are central to AN. The following hypothesis will attempt to clarify their role in AN. Anorexia nervosa patients (ANs) have significantly lower core temperatures (Tcore) compared to healthy controls. This reduced temperature represents a reset Tcore that needs to be maintained. However, ANs cannot maintain this Tcore due primarily to a reduced basal metabolic rate (BMR); BMR usually supplies heat to sustain Tcore. Therefore, to generate the requisite heat, ANs revert to the behavioral-thermoregulatory strategy of HyAc. The majority of ANs (~89%) are reportedly HyAc. Surprisingly, engagement in HyAc is not motivated by a conscious awareness of low Tcore, but rather by the innocuous sensation of "cold- hands" frequently reported by ANs. That is, local hand-thermoreceptors signal the brain to initiate HyAc, which boosts perfusion of the hands and alters the sensation of "cold-discomfort" to one of "comfort." This "rewarding" consequence encourages repetition/habit formation. Simultaneously, hyperactivity increases the availability of heat to assist with the preservation of Tcore. Additionally, HyAc induces synthesis of specific brain neuromodulators that suppress food intake and further promote HyAc; this outcome helps preserve low weight and perpetuates this vicious cycle. Based on this hypothesis, and supported by rodent research, external heat availability should reduce the compulsion to be HyAc to thermoregulate. A reduction in hyperactivity should decrease the production of brain neuromodulators that suppress appetite. If verified, it is hoped that this hypothesis will assist with the development of novel treatments to aid in the resolution of this intractable condition.